Study on aerodynamic characteristics of tilting wing unmanned aerial vehicle in transition state - MA Kai; LIN Changliang; PAN Minglong; WANG Xiong; LU Yang (Hangkong gongcheng jinzhan)
In response to the problem of the continuous tilting transition process of the configuration of unmanned aerial vehicle with complex and unsteady aerodynamic characteristics, the real blade is replaced with a virtual propeller disk model, the rotor flow field is calculated by adding momentum source terms. The dynamic grid technology is combined to perform unsteady aerodynamic simulation of the flow field. The aerodynamic interference and lift resistance characteristics of the flow field near the rotor/fixed wing are calculated and analyzed, and the model is established and the forward flight speed tilt angle motion equation is iteratively fitted for the transition section motion state. The results show that the initial tilting state of the unmanned aerial vehicle is less affected by the downwash flow of the rotor, and the main lift is provided by the fixed wing. During the tilting process at a tilt angle of 30°~50°, the resistance of the tilting rotor wing section increases, and the required pulling force of the rotor increases.The lift of the outer section of the tilting wing decreases due to the interference of the downwash flow of the rotor,and the main lift effect is borne by the rotor in the final stage of tilting.